Lifetime risk of common neurological diseases in the elderly population. Issue 2 (2nd October 2018) - Licher, Silvan; Darweesh, Sirwan K L; Wolters, Frank J; Fani, Lana; Heshmatollah, Alis; Mutlu, Unal; Koudstaal, Peter J; Heeringa, Jan; Leening, Maarten J G; Ikram, M Kamran; Ikram, M Arfan
Abstract : Objective: To quantify the burden of common neurological disease in older adults in terms of lifetime risks, including their co-occurrence and preventive potential, within a competing risk framework. Methods: Within the prospective population-based Rotterdam Study, we studied lifetime risk of dementia, stroke and parkinsonism between 1990 and 2016. Among 12 102 individuals (57.7% women) aged ≥45 years free from these diseases at baseline, we studied co-occurrence, and quantified the combined, and disease-specific remaining lifetime risk of these diseases at various ages for men and women separately. We also projected effects on lifetime risk of hypothetical preventive strategies that delay disease onset by 1, 2 and 3 years, respectively. Results: During follow-up of up to 26 years (156 088 person-years of follow-up), 1489 individuals were diagnosed with dementia, 1285 with stroke and 263 with parkinsonism. Of these individuals, 438 (14.6%) were diagnosed with multiple diseases. Women were almost twice as likely as men to be diagnosed with both stroke and dementia during their lifetime. The lifetime risk for any of these diseases at age 45 was 48.2% (95% CI 47.1% to 51.5%) in women and 36.2% (35.1% to 39.3%) in men. This difference was driven by a higher risk of dementia as the first manifesting disease in women than in men (25.9% vs 13.7%; p<0.001), while this was similar for stroke (19.0%vs18.9% in men) and parkinsonism (3.3% vs 3.6% in men). Preventive strategies that delay disease onset with 1 to 3 years could theoretically reduce lifetime risk for developing any of these diseases by 20%–50%. Conclusion: One in two women and one in three men will develop dementia, stroke or parkinsonism during their life. These findings strengthen the call for prioritising the focus on preventive interventions at population level which could substantially reduce the burden of common neurological diseases in the ageing population.